The Relationship between Career Path and Job Satisfaction of Nurses in the Inpatient Room of X Hospital, Bekasi Regency - Lestari, Prita; Sapeni, Muhammad Al-Amin R.; Lastriyanti, Lastriyanti (An Idea Health Journal, 2024)
Job satisfaction based on nurse competency, specifically the ability of nurses to manage, keep a low profile, work stress and inefficiency cause inpatient nurses to feel dissatisfied at work. The State of Indonesia, to be exact, in the city of Solok in 2019, job dissatisfaction reached 51.6% and in one of the hospitals in the city of Makassar it was around 51.6%, and inpatient nurses, especially in the city of Palembang, had not received 52.7% job satisfaction. The purpose of this study was to determine the relationship between career path and job satisfaction of nurses in the inpatient room of X Hospital, Bekasi Regency. This research is a descriptive research with a quantitative approach and a cross sectional research design. Data collection, primary data obtained by direct collection consisting of the number of nurses and career level and through filling out career path questionnaires consisting of two sections of clinical nurse I and clinical nurse II which are observational, filling out the job satisfaction questionnaire Job Satisfaction Scale (JSS) on an ongoing basis direct. Data processing using a computer system and data analysis using SPSS with Chi-Square Test. The results showed that there was no relationship between career path and nurse job satisfaction in the inpatient room of X Hospital, Bekasi Regency, which indicated a p-value of 0.551, where the number > ? = 0.05. The level of career competence is not related to the sense of job satisfaction that nurses have in the inpatient room of X Hospital, Bekasi Regency.